THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE WORK ACHIEVEMENT AT EDUCATION OFFICE OF NORTH SUMATERA PROVINCE - Darwis, Darwis; Matondang, Sofiyan; Sianturi, Marudut (JURNAL PROINTEGRITA, 2020)
This study aims at implementing work discipline, work motivation, and job performance at the Education Office of North Sumatra Province, the influence of work discipline on work performance at the Education Office of North Sumatra Province, the influence of work motivation on job performance at Education Office of North Sumatera Province, the influence of work discipline and work motivation on job performance at Education Office of North Sumatera Province. The population of research is all employees at Education Department of North Sumatera Province in 2015 as many as 140 people. In this study, the confidence level was set 95% then the sample size (n) = 96.04 is about 96 people. Sample determination technique is stratified random sampling, that is samples taken from each section evenly, that is member of population divided by total of population multiplied by research sample. The work discipline has a positive and significant effect on the employee's performance as seen from the tcount of 7,000 > = 0.05, meaning that the high performance of employees in Education Office of North Sumatera Province is influenced by factors discipline. Work motivation has positive and significant effect on employee performance as seen from titung value of 7,305attable 1,986 (sig 0,000), which is significantly smaller than > = 0,05, meaning that the high of employee performance in Education Office of North Sumatera Province is influenced by factors motivation. Work discipline and work motivation have a positive and significant effect on employee performance as seen from the value of Fhitung 45,983attable 1,986 (sig 0,000), which is significant t less than > Ftable 3,09 with sig 0,000 <0,05. Adjusted R-Square value is 0.486, it is known that the contribution of work discipline and work motivation to work performance of 48.60%. This means that the variables of work discipline and work motivation contribute to work performance is 48.60% while the rest of 51.40%, contributed by other un-researched variables such as organizational culture, supervision, leadership, and others. In order for employees to further improve the discipline of work by coming and returning on time, and doing work in accordance with established work procedures, head section should be in upholding discipline so as not to discriminate between employees with one another. In order for employees to further improve the work motivation by not delaying the work to be completed, and to the head of the section should always provide encouragement or motivation by always giving attention in the form of awards to employees who excel or in the form of reprimands to employees who make mistakes in work. In order for employees to pay more attention to their work performance like doing the job that is given seriously and responsible for the work done.